2021
DOI: 10.3390/rs13101973
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Monitoring of Advancing and Surging Glaciers in the Tien Shan, 1990–2019

Abstract: The advancing of glaciers is a manifestation of dynamic glacial instability. Glaciers in the Tien Shan region, especially in the Central Tien Shan, show instability, and advancing glaciers have been recently detected. In this study, we used Landsat TM/ETM+/OLI remote sensing images to identify glaciers in the Tien Shan region from 1990 to 2019 and found that 48 glaciers advanced. Among them, thirty-four glaciers exhibited terminal advances, and 14 glaciers experienced advances on the tributary or trunk. Ten of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 86 publications
2
23
0
Order By: Relevance
“…A previous study found that some glacier geometry variables (e.g., surface slope and glacier length) show statistically significant correlations with surging behavior [15]. However, to date, only three regions have been researched by glacier inventory, including Karakoram [8], Pamirs [9], and Tian Shan [12]. To advance the understanding of glacier surge characteristics and extend our predictive capabilities of regional-scale changes, using the outlines from RGI V6 [60], we analyzed differences in area, slope, range of elevation, and length between STGs and non-STGs in the HMA.…”
Section: Surge Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that some glacier geometry variables (e.g., surface slope and glacier length) show statistically significant correlations with surging behavior [15]. However, to date, only three regions have been researched by glacier inventory, including Karakoram [8], Pamirs [9], and Tian Shan [12]. To advance the understanding of glacier surge characteristics and extend our predictive capabilities of regional-scale changes, using the outlines from RGI V6 [60], we analyzed differences in area, slope, range of elevation, and length between STGs and non-STGs in the HMA.…”
Section: Surge Characteristicsmentioning
confidence: 99%
“…STGs throughout HMA have received significant attention in the past decades, for example, the Karakoram [8], Pamirs [9], West Kunlun Shan [10], Himalayas [11], and Tien Shan areas [12]. Although STGs account for only a small part of the HMA's glacier population, they can provide valuable insights into the triggering mechanisms of surge-type behavior and fast glacier flow [13].…”
Section: Introductionmentioning
confidence: 99%
“…Glacier length usually refers to the maximum length of a glacier centerline (main flow line) and represents the longest motion trajectory of a glacier, which is among the key determinants of glacier geometry and a basic parameter of glacier inventories (RGI Consortium, 2017) and modeling (Maussion et al, 2019). Glacier length fluctuations can be used to quantify glacier changes (Zhou et al, 2021a), such as by identifying glacier advancement, surge, or retreat. Glacier length fluctuations (e.g., Leclercq et al, 2014) have also been used to study the relationships with changes in glacier area (Winsvold et al, 2014) and the geometric structure of a glacier (Herla et al, 2017), estimate glacier volume in combination with the glacier area (Lüthi et al, 2010), and reconstruct annual averaged surface temperatures over the past 400 years on hemispherical and global scales (Leclercq and Oerlemans, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Affected by climatic change, most glaciers retreat and very few glaciers advance in the Tianshan Mountains [3,4,8,14], which affects the hydrological characteristics such as the quantity, seasonal distribution and temporal variability of the downstream rivers. Thus, it is necessary to quantify the impact of climate change on the variation of the glaciers and runoff under such a climatic background in the Tianshan Mountains.…”
Section: Introductionmentioning
confidence: 99%